Unlocking asylum seekers’ voices: protocol of a mixed-method clinical study on the use of the cultural formulation interview with asylum seekers in Belgium - Claus, Lukas; Schouler-Ocak, Meryam; Braakman, Mario H.; Sabbe, Bernard; Van Beuren, Godfried; van den Ameele, Seline (Frontiers in Psychiatry, 2023)
Background Despite a high prevalence of mental disorders among asylum seekers, many barriers to mental healthcare exist. Cultural and contextual factors strongly influence the experience and expression of psychological distress, putting asylum seekers at greater risk of misdiagnosis and inappropriate treatment. The Cultural Formulation Interview (CFI) is a useful tool to map out cultural and contextual factors of mental disorders; however, to the best of our knowledge, it has not yet been investigated in asylum seekers specifically. The primary aim of this study is to evaluate the value of the CFI in the psychiatric assessment of asylum seekers. Second, we will describe the themes relevant to psychiatric distress in asylum seekers that are identified by the CFI. In addition, asylum seekers’ experience of the CFI will be evaluated. Methods and analysis This cross-sectional, mixed-method clinical study aims to recruit a group of 60–80 asylum seekers (age 15–29) with mental health symptoms. Data will be collected using structured (MINI, PCL-5, HDRS-17, WHOQoL-BREF & BSI) and semi-structured (CFI & CFI-debriefing) questionnaires to assess cultural background, contextual factors, and illness severity. Multidisciplinary case discussions will be held after the completion of interviews, following a methodological stepped approach. Combining qualitative and quantitative research techniques, this study aims to generate reliable knowledge on working with the CFI in asylum seekers. Based on the findings, recommendations for clinicians will be developed. Discussion This study addresses the knowledge gap on using the CFI in asylum seekers. Compared to prior studies, it will provide new insights into the use of the CFI in the specific context of working with asylum seekers. Ethics and dissemination Prior research on the CFI in asylum seekers is limited, partly because of their high vulnerability and low access to care. The study protocol has been tailored in close collaboration with several stakeholders and validated after piloting. Ethical approval has already been obtained. Together with the stakeholders, the results will be translated into guidelines and training materials. Recommendations to policymakers will also be provided.